κ-carrageenan oligosaccharides alleviate MDP induced rumen epithelial cell inflammatory damage by inhibiting the activation of NOD2/NF-κB pathway - Xiao, Yimei; He, Xiaolin; Ma, Jian; Du, Chunmei; Gan, Shangquan; Yin, Fuquan (Frontiers in Veterinary Science, 2025)
IntroductionUnder Subacute Ruminal Acidosis (SARA) conditions, harmful substances released by the massive lysis of ruminal bacteria are further degraded into small bacterial peptides, such as muramyl dipeptide (MDP). These degradation products are absorbed through the rumen wall and enter the bloodstream continuously, triggering a series of nutritional metabolic diseases and systemic pro-inflammatory responses. Therefore, inhibiting MDP-induced damage emerges as a novel target for preventing and alleviating SARA. Nutritional regulation serves as a critical strategy for enhancing the body’s resistance to inflammatory challenges. Moreover, plant-derived oligosaccharide extracts offer a promising approach for the prevention and control of animal diseases.MethodsIn this study, the protective effects and possible molecular mechanisms of κ-carrageenan oligosaccharides (KOS) against MDP-induced damage in ovine ruminal epithelial cells (ORECs) were evaluated. The CCK8 assay, western blot analysis, ELISA, and PCR were employed in this study.ResultsThe results demonstrated that exposing ORECs to 25 μg/mL MDP for 6 h induced inflammatory damage. In contrast, pretreatment of ORECs with 75 μg/mL KOS for 9 h significantly enhanced cell viability, downregulated pro-inflammatory cytokine levels, restored immunoglobulin concentrations, reduced apoptosis rates, and regulated the expression of apoptosis-related genes under MDP stimulation. KOS exerted anti-inflammatory effects by scavenging ROS, improving tight junction barrier function, and inhibiting activation of the NOD2/NF-κB signaling pathway.ConclusionPretreatment with 75 μg/mL KOS for 9 h effectively alleviated MDP-induced inflammatory damage in ORECs by inhibiting the activation of the NOD2/NF-κB pathway.